Measurement of the bb[bar] dijet cross section in pp collisions at √s = 7 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (The European physical journal. C, Particles and fields, 2016)
The dijet production cross section for jets containing a b-hadron (b-jets) has been measured in proton–proton collisions with a centre-of-mass energy of \(\sqrt{s} = 7\) TeV, using the ATLAS detector at the LHC. The data used correspond to an integrated luminosity of \(\mathrm 4.2\,\text {fb}^{-1}\). The cross section is measured for events with two identified b-jets with a transverse momentum \(p_{\text {T}} > 20\) GeV and a minimum separation in the \(η \)–\(φ \) plane of \(Δ R = 0.4\). At least one of the jets in the event is required to have \(p_{\text {T}} > 270\) GeV. The cross section is measured differentially as a function of dijet invariant mass, dijet transverse momentum, boost of the dijet system, and the rapidity difference, azimuthal angle and angular distance between the b-jets. The results are compared to different predictions of leading order and next-to-leading order perturbative quantum chromodynamics matrix elements supplemented with models for parton-showers and hadronization.